A Facile Hg2+‐related Quenching Photoluminescence Sensor Based on Nitrogen‐doped Graphene Quantum Dots. (3rd September 2020) - Du, Shi‐Man; Shang, Bing‐Bing; Zhang, Xiao‐Ru; Feng, Fu; Zhang, Sheng‐Hui; Qi, Bao‐Ping
Abstract : A Hg 2+ ‐related quenching photoluminescence (PL) sensor was fabricated based on nitrogen‐doped graphene quantum dots (N‐GQDs) as the luminescent agent and glutathione as the masking agent to detect Hg 2+ in tap water. The addition of Hg 2+ significantly reduced the PL intensity of N‐GQDs, which was attributed to coordination reaction inducing the aggregation of N‐GQDs. The Hg 2+ ‐related quenching PL sensor with glutathione as the masking agent has good selectivity and accuracy. The sensor showed a linear relationship ranging from 0.5 to 110 nM with the detection limit 0.08 nM (S/N = 3). The proposed method was applied to the determination of Hg 2+ in tap water, and the results were consistent with atomic absorption spectroscopy (AAS). Abstract : The description of photoluminescence from nitrogen‐doped graphene quantum dots quenched by Hg 2+ .